Studi Motion Sickness Incidence (Msi) Pada Kapal Patroli (Kal-28) Katamaran - Muhammad Thareq Maulana; Bagyo Suwasono; Didik Harianto; Sutiyo Sutiyo; Ali Munazid (Departemen Teknik Kelautan Universitas Hasanuddin, 2024)
On a Ship seasickness (motion sickness) is a condition caused by the movement of a ship that results in dizziness, nausea, and vomiting. The Motion Sickness Incidence (MSI) Study on the Patrol Catamaran (KAL-28) aims to evaluate the comfort level of passengers and the safety of the ship's crew during operations, following the ISO 2631/1997 standards. The evaluation is conducted on the vertical acceleration response of the ship under various wave conditions, speeds, and wave directions. Mapping is performed in various areas of the ship, including the deck, navigation room, and engine room, considering wave heights of 0.875 meters and 2 meters at speeds of 15 knots, 22.5 knots, and 30 knots. The research results indicate that at a speed of 15 knots, the deck area, navigation room, and engine room meet the criteria from comfortable to somewhat uncomfortable. However, at speeds of 22.5 knots and 30 knots, these areas are rated as somewhat uncomfortable to very uncomfortable. This study emphasizes the need for ship design that considers both passenger comfort and safety, especially for patrol catamarans.